1988
DOI: 10.1016/0092-8674(88)90123-7
|View full text |Cite
|
Sign up to set email alerts
|

The sequence specificity of homeodomain-DNA interaction

Abstract: SummaryThe Drosophila developmental gene, engrailed, encodes a sequence-specific DNA binding activity. Using deletion constructs expressed as fusion proteins in E. coli, we localized this activity to the conserved homeodomain (HD). The binding site consensus, TCAATTAAAT, is found in clusters in the engrailed regulatory region. Weak binding of the En HD to one copy of a synthetic consensus is enhanced by adjacent copies. The distantly related HD encoded by fushi tarazu binds to the same sites as the En HD, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
334
2
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 483 publications
(340 citation statements)
references
References 65 publications
3
334
2
1
Order By: Relevance
“…Although in vitro studies suggested cooperative binding, the major effect was seen between one and two copies. An increase from four to six copies only marginally improved in vitro binding 9 . Perhaps site occupancy in vivo has a different dependence on the number of copies.…”
Section: Enhancer Strengthmentioning
confidence: 89%
See 4 more Smart Citations
“…Although in vitro studies suggested cooperative binding, the major effect was seen between one and two copies. An increase from four to six copies only marginally improved in vitro binding 9 . Perhaps site occupancy in vivo has a different dependence on the number of copies.…”
Section: Enhancer Strengthmentioning
confidence: 89%
“…The homoeodomain-binding site used to demonstrate ftz-dependent activation is also bound by the en protein in vitro 8,9 . Nonetheless, when en producer plasmid was co-transfected with the responder constructs that are inducible by ftz, no activation occurred.…”
Section: Engrailed Represses Ftz Activationmentioning
confidence: 99%
See 3 more Smart Citations